Rho of Plant GTPase Signaling Regulates the Behavior of Arabidopsis Kinesin-13A to Establish Secondary Cell Wall Patterns([W]) - Oda, Yoshihisa (American Society of Plant Biologists, 2013)
Plant cortical microtubule arrays determine the cell wall deposition pattern and proper cell shape and function. Although various microtubule-associated proteins regulate the cortical microtubule array, the mechanisms underlying marked rearrangement of cortical microtubules during xylem differentiation are not fully understood. Here, we show that local Rho of Plant (ROP) GTPase signaling targets an Arabidopsis thaliana kinesin-13 protein, Kinesin-13A, to cortical microtubules to establish distinct patterns of secondary cell wall formation in xylem cells. Kinesin-13A was preferentially localized with cortical microtubules in secondary cell wall pits, areas where cortical microtubules are depolymerized to prevent cell wall deposition. This localization of Kinesin-13A required the presence of the activated ROP GTPase, MICROTUBULE DEPLETION DOMAIN1 (MIDD1) protein, and cortical microtubules. Knockdown of Kinesin-13A resulted in the formation of smaller secondary wall pits, while overexpression of Kinesin-13A enlarged their surface area. Kinesin-13A alone could depolymerize microtubules in vitro; however, both MIDD1 and Kinesin-13A were required for the depolymerization of cortical microtubules in vivo. These results indicate that Kinesin-13A regulates the formation of secondary wall pits by promoting cortical microtubule depolymerization via the ROP-MIDD1 pathway.